New Approaches in Sensing and Targeting Bacterial rRNA A-site - Parameswaran, Preethi; Ranjan, Nihar; Flora, Swaran J.S. (Medicinal Chemistry, 2021)
New chemical agents that could combat increasing antibiotic resistance are urgently needed. In this mini-review, an old but highly relevant RNA sequence which is crucial for the continuation of bacterial life-cycle is covered. Some of the most significant advances of the last decade in sensing and targeting the bacterial rRNA A-site: a well-validated binding site of proverbially known aminoglycoside antibiotics are described. Some of the major advances in direct sensing of the bacterial decoding side (A-site) are described and also new fluorescent molecules that are capable of detecting lead compounds through high-throughput assays by displacement of fluorescent probe molecules are highlighted. Lastly, some of the recently discovered non-aminoglycoside small molecule binders of bacterial rRNA A-site as a new class of molecules that could provide future scaffolds and molecules for developing new antibacterial agents have been discussed.
Keywords: FRET